Sleep health and its related influencing factors in primary and middle school students in Fuzhou: A large multi-center cross-sectional study - Xu, Xingyan; Zheng, Fuhao; Cai, Yingying; Lin, Jie; Zeng, Zhaonan; Wei, Shichao; Wu, Siying (Frontiers in Public Health, 2022)
Background This current study set out to investigate the status of sleep health in 7–20-year-old students in Fuzhou and explore the related influencing factors of sleep health. Methods A total of 38,467 children and adolescents in Fuzhou were included in the study through a random stratified cluster sampling. Data were collected from May to June 2019, in 18 primary schools and 18 middle schools from nine districts, Fuzhou. Children's parents and adolescents of sampled classes were invited to fill out a series of questionnaires about the performance of the last 6 months (sociodemographic characteristics, sleep-related lifestyle behaviors, and electronic-products usage). Multiple linear regression was carried out to analyze data. Results Of the total 40,888 questionnaires we released, 38,467 were valid and effective with the response rate was 94.08%. The age of the surveyed participants was 11.85 ± 3.1, including 20,013 boys and 18,454 girls. The multiple linear regression analysis identified factors associated with sleep health (p < 0.05): Boy (coef = 0.073, 95% CI: 0.030–0.115), age (coef = 1.797, 95% CI: 0.224–0.243), key school (coef = 2.069, 95% CI: 0.105–0.193), urban (coef = 0.096, 95% CI: 0.054–0.139), excessive daytime sleepiness (coef = 0.535, 95% CI: 0.432–0.639), unhealthy sleep habits (coef = 0.363, 95% CI: 0.307–0.419), eating before sleep (coef = 0.578, 95% CI: 0.527–0.630), using electronic products in bedroom (coef = 0.074, 95% CI: 0.028–0.121), screen time per day during school (coef = 0.260, 95% CI: 0.235–0.284), frequency of using electronics 30 min before bedtime (coef = 0.150, 95% CI: 0.134–0.166), strained relationship with parents (coef = 0.361, 95% CI: 0.270–0.452), strained relationship with peers (coef = 0.267, 95% CI: 0.171–0.363), excessive homework or learning (coef = 0.189, 95% CI: 0.141–0.237), time for doing homework (coef = 0.266, 95% CI: 0.245–0.287), and mood swings frequently (coef = 1.174, 95% CI: 1.127–1.221) negatively impact sleep health. Sleep alone (coef = −0.204, 95% CI: −0.262–0.147) were the risk factors for sleep health. Furthermore, frequent mood swings was considered the most influential factor on overall variables. Conclusions Sleep health is associated with factors covered sociodemographic characteristics, family sleep habits, and routine activities before bedtime. Multiple measures should be taken to improve sleep quality in a targeted manner.